Pengaruh Karakteristik Perusahaan Terhadap Profitabilitas Pada Perusahaan Manufaktur Tahun 2018-2020 - Ayu Lestari; Ceacilia Srimindarti (Universitas Pendidikan Ganesha, 2022)
This study aims to test and analyze the influence of company characteristics on profitability. The population used in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The sampling method used in this study is purposive sampling techniques and get samples 445 companies. The data analysis method used in this study is multiple linear regression analysis. The results of this study found that institutional ownership and company size positively affect profitability. Managerial ownership has a significant negative effect on profitability, while liquidity has no effect on profitability.